Micron-sized secondary Si/C composite with in situ crosslinked polymeric binder for high-energy-density lithium-ion battery anode. (20th June 2019) - Feng, Kun; Li, Matthew; Zhang, Yining; Liu, Wenwen; Kashkooli, Ali Ghorbani; Xiao, Xingcheng; Chen, Zhongwei
Abstract: Nanonization has been proven to be an effective approach in countering the drawbacks associated with volume change of silicon anodes. Considering the demand from practical applications, which not only involves high capacity and good cycling stability, but also includes facile process, high tap density, etc., it is highly desirable to fully take advantage of nano-sized silicon, while circumvent the side effects arisen from nanonization. We have successfully synthesized a micron-sized spherical composite (∼1–6 μm) via a facile spray-drying process, with nano-sized silicon embedded in a conductive matrix consisted of crosslinked binder and carbon. Volume change of silicon is largely buffered by the voids inside the structure, which secures silicon on its conductive network. More importantly, tap density of the secondary particle is three times that of the primary silicon nanoparticles, favoring its practical application in a lithium-ion battery. The composite displays a specific capacity of 1353 mAh g −1 after 500 cycles at 0.5C, which represents an 87% retention of its initial capacity. Full-cell lithium-ion batteries with the secondary composite and commercial cathode displays a high areal energy density of 10 mWh cm −2, while the thickness of the anode is only 1/3 that of commercial graphite electrode delivering the same areal energy density, which can be translated to a 39% increase in volumetric energy density in multi-stack batteries.